Design and Implementation of Automated irrigation system using ZIGBEE and GSM - Prof .S.S.Belsare, Mamta patidar, (International Journal of Scientific Research and Management (IJSRM), 2015)
The objective of this paper is to represent the Automated irrigation system using ZIGBEE and GSM foragricultural crop. In these system use the Wireless Technology. The system has represented the wireless sensor networkof soil-moisture, temperature and humidity sensor and water level sensor placed into root zone of the plant. Intraditional approach to measure these factors in an agricultural environment meant individuals manually taking measurements andchecking them at various times. This paper includes the monitoring of the system using zigbee and gsm.